In situ detection of alkaline phosphatase in a cisplatin-induced acute kidney injury model with a fluorescent/photoacoustic bimodal molecular probe - Chen, Xingwang; Yuwen, Zhiyang; Zhao, Yixing; Li, Haixia; Chen, Kang; Liu, Hongwen (Frontiers in Bioengineering and Biotechnology, 2022)
Kidneys are an important way of drug metabolism and excretion. The high local concentration of drugs or drug allergy, generally causes acute kidney injury (AKI). Finding out effective biomarkers of initial stage of AKI and constructing activable molecular probes with excellent detection properties for early evaluation of AKI remains a huge significance and challenge. Alkaline phosphatase (ALP), a key hydrolyzed protease, exists in the epithelial cells of kidney and will be discharged into the urine following kidney injury. However, no studies have revealed its level in drug-induced AKI. The existing ALP fluorescent molecular probes are not suitable for testing and imaging of ALP in the AKI model. Drug-induced AKI is accompanied by oxidative stress, many works have indicated that a large amount of ROS will boost in AKI model. Thus, the probe used for imaging of AKI should be chemical stable toward ROS. But most previous NIR fluorescent ALP probes are not stable towards ROS in the AKI model. Hence, we built a chemical-stable molecular sensor (CS-ALP) to map ALP level in cisplatin-induced AKI. This novel probe would not be destroyed by ROS generating in the AKI model, thus afford a high-fidelity imaging result. In the presence of ALP, probe CS-ALP generates a new absorbance peak at 685 nm and fluorescent emission peak at 716 nm, respectively, which could be transformed into “turn-on” photoacoustic (PA) and near infrared fluorescent (NIRF) imaging of ALP in AKI. CS-ALP could quickly enrich at kidneys, thus CS-ALP was successfully applied for NIRF/PA bimodal in vivo imaging. Finally, combining the NIRF/PA bimodal imaging results, we conclude that upregulated expression of ALP will occur at the early stage of AKI and will continue to express with the aggravation of AKI.